Increasing Serum Troponin I and Early Prognosis in Patients with Chest Pain or Angina Equivalent Symptoms in the Emergency Department - HH Davarani; M AfzaliMoghadam; H Hosseinnejad; R Hamidian (Tehran University of Medical Sciences, 2012)
Background: The purpose of this research was to determine the relation between negative or positive qualitative troponin I test and the short term prognosis of patients presenting to emergency department with chest pain or angina equivalent symptoms. Methods: we assessed the qualitative rapid troponin I in patients with chest pain or angina equivalent symptoms after at least 4 hours and then we followed the patients in 72 hours after presentation for adverse events such as death, CCU admission, fatal arrhythmias and heart failure. Results: After comparing qualitative troponin I test results and adverse events, we concluded that the troponin I was significantly more positive in patients with adverse events (i.e. CCU admission, fatal arrhythmias and heart failure) (P=0.031). Conclusion: A single measurement of  rapid qualitative troponin I test can be used as a prognostic factor in patients with chest pain or angina equivalent symptoms and also as a device for risk stratification of moderate and high risk patients.